Meningkatkan Kemampuan Kader Lansia Melalui Pelatihan Skreening Barthel Index, Abbreviated Mental Test Dan Geriatric Depression Scale - Endy Nurhayati; Reny Nurulaini; Husnul Khotimah; Ika Nofiana (Universitas Tribhuwana Tunggadewi, 2021)
Elderly cadres have an important role in screening the health of the elderly. However, the role of elderly cadres in Sumberporong Village is not optimal. One of the contributing factors is the ability of cadres to use geriatric instruments is still very low.. The purpose of this study was to determine the effectiveness of geriatric tools online training on the ability of cadres to perform screening. Method. The research design used a one group post test only design. The population in this study were elderly cadres in Sumberporong Village, Lawang. A sample of 32 respondents was taken by cluster sampling technique. The independent variable is geriatric tools online training and the dependent variable is the screening ability of elderly cadres. The research instrument used a questionnaire. Data analysis using one sample t test with = 0.05. Results. The results showing that geriatric tools online is affective for improving the ability of elderly cadres for doing screening in Sumberporong Village, Lawang (p = 0.000; = 7.5; SD = 2.229). Conclusion. Geriatric tools online training are very important given to the elderly cadres in order to improve their ability for doing elderly screening.